Water scarce or water abundant? The case of Can Tho, Vietnam. Issue 7 (9th August 2019) - Allen, Sarah
ABSTRACT: Demand for water resources has increased globally along with concerns over its protection, usage and potential scarcity. The location of abundant water sources do not always coincide with where large quantities of people reside. As such, many regions live with the threat of water shortages. Interpretations of water scarcity from international, national and regional scales of analysis are projected onto water availability at the local scale due to large, and often intimidating, global facts. This article looks at the periurban area of Can Tho, Vietnam, to argue that the discourse around water scarcity creates the impression of a water crisis. A local scale analysis reflects that residents of Can Tho have the knowledge to use local water resources in many different ways, thus ensuring their personal water security. The assessment of water scarcity at the national and international scale does not translate to Can Tho's current situation.